The role of S100A1 in external auditory canal cholesteatoma - Naim, Ramin; Hörmann, Karl (Oncology reports, 2006)
S100 proteins were reported to be involved in different biological activities such as transduction of intracellular calcium signalling. It has been reported that each member of the S100 protein family exhibits a distinct tissue-specific pattern of expression. Furthermore, altered S100 protein expression and function correlate with many diseases. The expression of S100A1 was reported to be increased in different tissue with hyperplasia. The external auditory canal cholesteatoma (EACC) is a benign hyperplasia of the auditory meatal skin. However, without treatment, EACC destroys adjacent tissue. Seventeen EACC specimens were collected and investigated immunohistochemically against S100A1. Normal auditory meatal skin served as control. In the EACC, S100A1 showed a more homogeneous staining pattern, positively expressed throughout the epithelial layers. The keratin debris showed no detectable expression of S100A1. In the auditory meatal skin (control), S100A1 was only expressed in the basal layer of the epithelium. We showed that there are different staining patterns in normal auditory meatal skin, middle ear cholesteatoma and external auditory canal cholesteatomas. The immunoreactivity increased with the stage of the disease. Contrary to that reported previously in the middle ear cholesteatomas, the reactivity was strongest in the upper epithelial layers. In our collective, the epithelial matrix of the EACC showed strong reactivity throughout all the layers. Surprisingly, there is no study regarding the connection between growth factors and S100A1. In previous experiments we showed significant increase of growth factors in EACC. This correlates with our new data concerning S100A1. This is the first study to show the different reactivity pattern of S100A1 in the external auditory canal cholesteatoma.
Gesehen am 11.03.2022